A 'big data' approach to global freshwater mussel diversity (Bivalvia: Unionoida), with an updated checklist of genera and species. (5th February 2021) - Graf, Daniel L; Cummings, Kevin S
ABSTRACT: The objective of this review is to update our previously published checklist of Recent freshwater mussel species and genera (Graf & Cummings, 2007, J. Molluscan Stud. : 291–314) to reflect the new data and research findings that have accumulated over the last decade. The MUSSEL Project Database was developed to synthesize the available taxonomic nomenclature, species ranges and published taxonomic hypotheses on genus–species combinations and synonymy. We have found 4, 988 available species-group level nominal species representing 958 valid species in 192 genera worldwide, an increase of 118 species since 2007. The current patterns of species richness are discussed with regard to both taxonomy and geography, as is the general flux in the number of species recognized over time. A checklist is provided herein, with a bibliography to key faunistic and taxonomic references. The full dataset is maintained and updated on the MUSSEL Project Web Site (http://mussel-project.net/ ).